2012
DOI: 10.1007/s00299-012-1354-5
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of miniature potted rose (Rosa hybrida cv. Linda) with P SAG12 -ipt gene delays leaf senescence and enhances resistance to exogenous ethylene

Abstract: KEY MESSAGE : The P ( SAG12 ) -ipt gene was transferred to miniature rose, as the first woody species, resulting in increased ethylene resistance due to specific up-regulation of the ipt gene under senescence promoting conditions. Transgenic plants of Rosa hybrida 'L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Our data showed that transformation of ramie with the P SAG12 ‐ ipt gene delayed leaf senescence and enhanced biomass. Roses and stay‐green lines have been obtained with similar features to those described in the present paper for ramie 29. Because of the worldwide economic importance of ramie, the decreased senescence observed in transgenic P SAG12 ‐ ipt ramie has commercial value.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Our data showed that transformation of ramie with the P SAG12 ‐ ipt gene delayed leaf senescence and enhanced biomass. Roses and stay‐green lines have been obtained with similar features to those described in the present paper for ramie 29. Because of the worldwide economic importance of ramie, the decreased senescence observed in transgenic P SAG12 ‐ ipt ramie has commercial value.…”
Section: Resultssupporting
confidence: 73%
“…Ethylene is known to promote the leaf senescence process 29. To confirm that leaf senescence was delayed in ipt ‐overexpressing plants, an ethephon‐induced leaf senescence test was conducted using the above two ipt ‐overexpressing plants (T19 and T20) and WT plants.…”
Section: Resultsmentioning
confidence: 99%
“…The construct SAG12::IPT gene has been studied in different species and all showed delayed senescence. This strategy was effective in delaying leaf senescence in several crops such as alfalfa ( Medicago sativa ; Calderini et al, 2007), broccoli ( Brassica oleracea ; Chen et al, 2001), cassava ( Manihot esculenta ; Zhang et al, 2010), creeping bentgrass ( Agrostis stolonifera ; Xu et al, 2009), lettuce (McCabe et al, 2001), petunia (Chang et al, 2003), rose ( Rosa hybrid ; Zakizadeh et al, 2013), tobacco (Jordi et al, 2000), and wheat ( Triticum aestivum ; Sýkorová, 2008). The senescence delay reduced ethylene biosynthesis in the transformed plants.…”
Section: Leaf Senescencementioning
confidence: 99%
“…The overproduction of cytokinins in petunia flowers transformed with P -S AG12- IPT has been reported to delay corolla senescence and decrease sensitivity to ethylene (Chang et al, 2003). The PSAG12-IPT gene was also transferred to a miniature rose, as the first woody species to be transformed with SAG12-IPT system, resulting in increased ethylene tolerance due to specific up-regulation of the IPT gene under senescence promoting conditions (Zakizadeh et al, 2013). An increase in ethylene, in petunia flowers exogenously treated with cytokinin, was found during senescence, and the lack of a negative effect can be explained considering the expression of the ethylene receptors was down-regulated by treatment with BA (Trivellini et al, 2015).…”
Section: Flower Senescencementioning
confidence: 99%
“…Specific upregulation of ipt gene under conditions favouring senescence in roses transformed with fusion gene, PSAG12-ipt resulted in better post-harvest life as transgenic plants showed resistance to early leaf senescence and ethylene production 28 . Progressing towards the advancement in transgenic breeding, several novel technologies like nextgeneration sequencing methods (NGS), parallel detection of SNPs via chip technologies, targeted mutagenesis via designer nucleases and related methods have boosted research in many model as well as non-model plants 19 , and have also provided possible avenues for advancement in rose breeding.…”
Section: Rose (Rosa Hybrida)mentioning
confidence: 99%